The Role of the Prefrontal Cortex in Pain Modulation - Ahmad, A (2012)
Existing knowledge identifies the prefrontal cortex (PFC) as the modulatory area for pain. Previous neuroimaging studies suggest the existence of the cortico-cortical pathway, an alternative pain modulatory pathway distinct from the descending modulatory pathway of pain. However, little is known of the extent, mechanism and underlying substrate of the modulation. The objective of this study is therefore to explore the role of the PFC in pain modulation. To examine the extent of PFC involvement in pain, meta-analyses of imaging studies in healthy volunteers and patients with chronic pain were performed. Using Gaussian-process regression (GPR) analysis, brain maps were produced from foci of activation as reported in the studies. Since structure dictates function, our next study was to performprobabilistic tractography on diffusion-weighted brain images to ascertain the connection probability of lateral PFC subdivisions and pain-related brain regions as well as intrinsic PFC connections. Two behavioural studies were conducted to investigate cognitive modulation of pain. The first was a study to assess the subjective and physiological correlates of cognitive stress, as previously used in stress-induced analgesia studies. The second was to investigate the involvement of the endogenous opioid system inthe cognitive modulation of pain through effortful reappraisal and contextual modulation. Meta-analyses in healthy volunteers and chronic pain patients revealed activation mainly in the lateral aspect of the PFC due to pain. Distinct pattern of activation was demonstrated in patients with significant ventrolateral PFC (VLPFC) activation across subtypes of chronic pain. Probabilistic tractography further illustrate the functional significance of lateral PFC subdivisions by demonstrating differential connection probability to pain-related brain regions; dorsolateral PFC (DLPFC) regions displayed higher connection probability with brain regions serving more sensory-discriminative function while VLPFC showed high connection probability with both sensory-discriminative and affective regions. Behavioural study of stress showed that cognitive stress failed to induce significant increases in biomarkers of stress, and was not affected by increased level of difficulty. Lastly, behavioural study on contextual modulation and reappraisal confirmed opioid mediation for contextual modulation while negating its involvement in effortful reappraisal. Findings from this studyillustrate the extent of PFC involvement in pain modulation especially in chronic pain patients and provide further evidence of an alternative pathway distinct from the opioid-mediated descending inhibitory pathway.